UPAYA MENINGKATKAN MOTIVASI BELAJAR MATERI LARI JARAK MENENGAH PADA PESERTA DIDIK MELALUI PEMBELAJARAN BERBASIS WEB DI KELAS X MIA 7 SMA NEGERI 11 AMBON - Malawere, Kristofel Aditya; Rachman, Gazali; Apituley, Patresia Silvana (Universitas Pattimura, 2024)
One of the innovations of learning media in the digital era is web-based learning media. Web-based learning media is a learning process that has a significant influence on the transformation of changes in the learning process in the current era. The method in this research is adjusted to the level of understanding of students, making it easier for students to learn more actively. Data were obtained through direct observation to determine student abilities. The results of the study showed that using the web-based learning method in the learning model can improve student learning motivation results with the results of 84.7% of students achieving the Minimum Completion Criteria (KKM). This study shows that it has a positive impact on student abilities and encourages student motivation and interest in improving student learning outcomes.